Using Pichia pastoris to produce recombinant glycerol kinase - Terrazas, Werner Damião Morhy; Aizemberg, Raquel [UNESP]; Gattas, Edwil Aparecida de Lucca [UNESP] (My University, 2014)
The methylotrophic yeast Pichia pastoris has been developed into an efficient expression system for the production of recombinant protein under the tight control of the methanol-induced alcohol oxidase promoter (pAOX1). In this study, a 2.5-liter culture system was developed for the growth of a P. pastoris strain bearing the GUT1 gene from Saccharomyces cerevisiae for the expression of recombinant glycerol kinase (GK). The best culture conditions to produce high levels of secreted GK were investigated by growing the recombinant strain of P. pastoris in shake flasks and a fermenter. Cell growth and enzyme production were found to be optimal after two days of growth. Enzyme production was affected by the nitrogen source, Difco peptone being the most appropriate for this purpose. Three different rates of air flow (1 to 3 L/min) were tested to observe their effect on cell growth and the secretion of GK into a medium containing 1% methanol as the sole carbon source. Increasing the rate of air bubbling in the culture medium enhanced both cell growth and GK activity, reaching a dry biomass of 7.84 mg/mL, cell viability of 98.4% and a maximal GK activity of 1.57 U/ mL, at a flow rate of 2.0 L/minute, at 30° C and pH 6.0. Moreover, the enzyme activity in the P. pastoris culture medium was 2.3 times higher under these conditions than in the shake-flask culture, demonstrating the significant influence of aeration on biomass production and GK activity secreted by P. pastoris.

A levedura metilotrófica Pichia pastoris possui um sistema de expressão eficiente para a produção de proteínas recombinantes. A indução da produção da proteína de interesse é feita com metanol, que é capaz de ativar a transcrição do gene de interesse clonado sob controle do promotor do gene AOX1. Um meio de cultura de 2.5 litros foi elaborado para o crescimento da cepa Pichia pastoris construída com o gene GUT1 de Saccharomyces cerevisiae para expressar a enzima recombinante glicerol quinase (GK). As condições ideais de cultura, para alcançar altos níveis de expressão de GK foram investigados em crescimentos realizados em frascos e fermentador. Crescimento celular e produção de enzima atingiram valores ótimos em dois dias de cultura. A produção enzimática foi afetada pela fonte de nitrogênio no meio. Peptona da marca Difco foi a fonte de nitrogênio mais adequada para a expressão desta enzima. Três diferentes concentrações (1-3 L / min) de fluxo de ar foram analisados em ensaios de crescimento celular e secreção da GK, no meio contendo 1 % de metanol como única fonte de carbono. O aumento do fluxo do ar no meio de cultura produziu melhores resultados para o crescimento celular e atividade da GK, atingindo 7,84 mg / mL de biomassa seca e 98,4% de viabilidade. A máxima atividade de GK foi de 1,57 U / mL, com a concentração de fluxo de ar de 2,0 L / minuto a 30 ° C e pH 6.0. O aumento da atividade enzimática foi 2,3 vezes maior no meio de cultura da Pichia pastoris nestas condições, revelando a influência deste parâmetro na produção de biomassa e atividade da GK.
Produção de glycerol quinase recombinante utilizando o sistema Pichia pastoris
Keywords: Pichia pastoris; Glycerol kinase; Oxygen; Biomass; Pichia pastoris; Glicerol quinase; Oxigênio; Biomassa